Passive smoking levels and related factors in non-smoking pregnant - Pektaş Danagöz, Ayşegül; Öner, Can; Çetin, Hüseyin; Şimşek, Engin Ersin (Journal of Dependence, 2020)
Objective: Passive smoking poses a serious risk for maternal, fetal and neonatal. In our study, it was aimed to determine passive smoking and affecting factors in pregnant women.Methods: This cross-sectional study was carried out with 290 pregnant women who applied to Gynecology and Obstetrics Clinic between 05.11.2018 and 05.01.2019. Data was gathered by face-to-face interview technique.Results: The study included women between the ages of 18-44 with a mean age of 28,2 ± 5,4. The median gestational weeks of participating women are 26 (min: 5-max: 41) weeks. Of the participants, 146 (50.3%) were exposed to cigarette smoking and 31 (10.6%) were sometimes exposed. 83% of the participants are exposed to smoking at home, 65.9% due to his wife. 145 people (50%) were non-smokers in their homes, 131 people (45.1%) were smoking in their rooms.Conclusion: Passive smoking rate was 50.3% in pregnant women. Factors causing this; pregnant women and their spouses having jobs or working in the private sector, being an extra person at home, not being disturbed by smoking, exposure to cigarette smoke by other people living in the house and at home, including the absence of house rules for smoking, being flexible or having more people living in the house.
Keywords: Pregnant; passive smoking; cigarette; environmental tobacco exposure